Depression in Post Disaster Societies: A Systematic Review - Reza Fithriy Insaniy; Atika Jatimi; Maulidiyah Junnatul Azizah Heru; Zainal Munir (Universitas Nahdlatul Ulama Surabaya, 2021)
Introduction: Disaster increases the risk of depression in individuals one to six years after the event. Objective:. This paper describes depression in post-disaster societies. Method: This study was a systematic review. Database searches included Google Scholar and Proquest, with the keywords post-traumatic, depression, and disaster. The article's criteria were in English, published in 2016-2020, and used (CES-D) questionnaire. This systematic review was based on Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Results: This study used 15 articles meeting the criteria. Analysis of fifteen articles showed that individuals had mental health burdens after a disaster occurs. One of them was depression. Conclusion: There is a depression in post-disaster societies. Future studies should explore the correlation between PTSD and depression after a disaster.